Corticosteroid use, myocardial injury and in‐hospital cardiovascular events in patients with community‐acquired pneumonia. Issue 1 (22nd July 2021) - Cangemi, Roberto; Carnevale, Roberto; Cammisotto, Vittoria; Nocella, Cristina; Bartimoccia, Simona; Taliani, Gloria; Falcone, Marco; Calvieri, Camilla; Pignatelli, Pasquale; Violi, Francesco; ,
Abstract : Background and Purpose: Corticosteroids are often prescribed to community‐acquired pneumonia (CAP) patients, but the relationship with major cardiovascular events (MACEs) is unclear. Experimental Approach: 541 CAP patients were recruited (334 males, mean age 71.9 ± 16.2 years). High‐sensitivity troponin T (hs‐cTnT) was measured at admission, during the hospital stay and at discharge. MACE occurrence was registered during a long‐term follow‐up. Key Results: Overall, 318 patients (59%) showed hs‐cTnT elevation >99th percentile (>0.014 μg/L). Age, heart failure and the increasing quintiles of hs‐cTnT (hazard ratio [HR] 2.16, 95% confidence interval [CI] 1.82‐2.58, P  < .001) predicted MACEs. Among patients with hs‐cTnT >0.014 μg/L at admission, 102 patients (31%) were on corticosteroids and showed lower hs‐cTnT increase ( P  = .021), (NADPH) oxidase‐2 (Nox2) activation ( P  = .005) and incidence of MACEs than untreated ones (HR 0.64, 95% CI 0.41‐0.97, P  = .038); no effect of corticosteroids on MACEs was observed in CAP patients with normal troponin. In vitro study showed that glucocorticoids have an antioxidant effect via downregulation of Nox2 activity. Conclusion and Implications: The study provides evidence that corticosteroid use is associated with lower increase of hs‐cTnT and incidence of MACEs in CAP patients.